Pendampingan Pelatihan Siaga Bencana Tanah Longsor Pada Kader di Desa Pargarutan Dolok Tahun 2026 - Nasution, Asmar Nauli; Fitriani, Fitriani; Awaliyah , Bintang Putri; Nainggolan , Tasya Amelia; Silaban, Maria Rejeki; Pakpahan, Moses; Nasution, Alya Fransiska; Napitupulu, Natar Fitri; Napitupulu, N.S Mastiur (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2026)
Background:Landslides are a disaster that often occurs in hilly areas with high rainfall. The community's lack of knowledge about mitigation increases the risk of losses and casualties. This community service activity aims to improve the knowledge and preparedness of cadres and the community of Pargarutan Dolok Village in facing landslides through mentoring and counseling activities. The activity was carried out on May 25, 2026 in Pargarutan Dolok Village, East Angkola District, South Tapanuli Regency, targeting village cadres and the local community. Methods:The methods used included delivering material, interactive discussions, questions and answers, and distributing leaflets regarding the causes, signs, impacts, and mitigation steps for landslides. Evaluation was carried out through observations of participant participation and their ability to understand the material provided. The activity went well and received active participation from all participants. Results:The results of the observations showed an increase in participants' understanding of the causes, early signs, impacts, and actions that need to be taken before, during, and after a landslide occurs. The enthusiasm of the participants during the discussion also showed an increase in public awareness of the importance of disaster mitigation and preparedness. Conclusion: These findings indicate that landslide preparedness training is effective in increasing the knowledge, awareness, and preparedness of cadres and the community regarding landslide risks. This activity is expected to be the first step in strengthening community capacity and supporting the creation of disaster-resilient villages through ongoing disaster education.